A method, product and application of preparing iodine-nitrogen-doped carbon quantum dots based on solvent-free pyrolysis
The preparation of iodine nitrogen-doped carbon quantum dots by solvent-free pyrolysis method solves the problems of cumbersome operation and safety hazards of traditional iron ion detection methods, and realizes low-cost and simple Fe3+ detection, with low detection limit and good fluorescence stability and selective.
Patent Information
- Application Number
- CN202410557578.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The prior art is complicated to operate, takes a long time, and requires high temperature, high pressure and a large number of solvents in iron ion detection, which poses safety risks, and the detection sensitivity and selectivity of traditional methods are insufficient.
Iodine nitrogen-doped carbon quantum dots were prepared by solvent-free pyrolysis method. The iodine nitrogen-doped carbon quantum dots were used as carbon and nitrogen sources, and the high stability and good water-soluble iodine nitrogen-doped carbon quantum dots were obtained through oil bath heating and dialysis, and the iodine nitrogen-doped carbon quantum dots were used. Its fluorescence quenching characteristics are established to establish the Fe3+ detection method.
It realizes low-cost, easy to operate and high safety iron ion detection, with a detection limit as low as 0.89μM, and is suitable for Fe3+ determination in environmental samples, avoids the use of high temperature, high pressure and large amounts of solvents, and has good fluorescence stability and Selective.
Smart Images

Figure HDA0004826525800000011 
Figure HDA0004826525800000021 
Figure HDA0004826525800000022
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon quantum dots, and in particular to a method, product and application of preparing iodine-nitrogen-doped carbon quantum dots based on a solvent-free pyrolysis method. Background Art
[0002] Iron is one of the essential trace elements in the human body. It is one of the main components of hemoglobin and heme and plays an important role in human health. Too little or too much iron in the human body can cause various diseases, such as anemia, Parkinson's syndrome, Alzheimer's disease, cancer, etc. At the same time, heavy metal ion pollution has become a threat to the environment. The increase in the content of iron ions in the environment has also become one of the problems that endanger human health. Therefore, the detection of iron ions in the environment is of great significance to both the environment and human health.
[0003] At present, there are many methods for determining iron, such as ultraviolet spectroscopy and atomic absorption spectrometry. However, most of these methods are cumbersome, time-consuming, and have high testing costs. Compared with these traditional detection methods, fluorescent nanomaterial detection has the advantages of high sensitivity, good selectivity, and easy operation. The traditional hydrothermal method for preparing carbon quantum dots usually requires a high temperature, high pressure environment and a large amount of solvent, which has certain safety hazards. The solvent-free pyrolysis method just solves this problem. The solvent-free pyrolysis method for preparing carbon quantum dots does not require solvents and generally reacts at normal pressure, which not only avoids safety hazards but also complies with the concept of green chemistry. In addition, carbon quantum dots also have the advantages of low toxicity, low preparation cost, good biocompatibility, and good stability. Therefore, Fe can be used. 3+ The fluorescence quenching property of carbon quantum dots was established to detect Fe 3+ The method was used to determine Fe in environmental samples. 3+ Determination. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method, product and application for preparing iodine-nitrogen-doped carbon quantum dots based on solvent-free pyrolysis. The method provided by the present invention avoids the shortcomings of traditional hydrothermal method that requires high temperature, high pressure and a large amount of solvent.
[0005] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing iodine-nitrogen-doped carbon quantum dots based on solvent-free pyrolysis, comprising the following steps:
[0006] The laver is ground into powder and then mixed with urea, heated in an oil bath under magnetic stirring, and then cooled to room temperature, deionized water is added to dissolve the solid, centrifuged, filtered, and dialyzed to obtain iodine-nitrogen doped carbon quantum dots.
[0007] In some embodiments, the laver is ground into powder by cooling the laver with liquid nitrogen and then grinding it into powder. The present invention does not specifically limit the grinding method, and any method known to those skilled in the art can be used.
[0008] In some embodiments, the mass volume ratio of the laver, urea, and deionized water is 0.1 g:5.0 g:30 mL.
[0009] In the present invention, urea only acts as a carrier for preparing carbon quantum dots, which is equivalent to the presence of a solvent, so it needs to be used in excess. The higher the proportion of urea, the more complete the reaction, and the unused urea will be removed in the subsequent dialysis step and will not affect the various properties of the product; the proportion of deionized water used will only affect the test of fluorescence intensity, and will not affect other factors. If the proportion of deionized water is high, the measured fluorescence intensity of the carbon quantum dots will be reduced.
[0010] In some embodiments, the oil bath heating temperature is 160-200°C, the time is 1-3h, preferably, the oil bath heating temperature is 160-180°C, the time is 1-2 hours, more preferably, the oil bath heating temperature is 180°C, the time is 2 hours.
[0011] In the present invention, when the heating temperature of the oil bath is lower than 160°C and the heating time is lower than 1 hour, the fluorescence performance of the prepared carbon quantum dots is not good enough; when the heating temperature of the oil bath is 180°C and the heating time is 2 hours, the optimal conditions are reached, and the fluorescence quantum yield of the obtained carbon quantum dots is the highest, and they have excellent fluorescence performance; when the heating temperature of the oil bath is higher than 180°C and the heating time is higher than 2 hours, the laver sample and the urea sample are partially burnt, and the product is lost. Therefore, the present invention is limited to the above parameter range.
[0012] In some embodiments, the centrifugation is performed at a speed of 3000-6000 rpm for 5-15 minutes. Preferably, the centrifugation is performed at a speed of 4000 rpm for 10 minutes.
[0013] In some embodiments, the filtration is performed using a 0.22 μm microporous filter membrane.
[0014] In some embodiments, the dialysis is performed using a 1000 Da dialysis membrane, and the dialysis time is 12-48 hours.
[0015] The present invention also provides iodine-nitrogen-doped carbon quantum dots prepared by the method for preparing iodine-nitrogen-doped carbon quantum dots based on solvent-free pyrolysis.
[0016] The present invention also provides the iodine-nitrogen doped carbon quantum dots as fluorescent probes in Fe 3+ Applications in the field of detection.
[0017] The present invention also provides a method for detecting Fe 3+ The method comprises adding the iodine-nitrogen doped carbon quantum dots to the sample to be tested, shaking and then standing, testing the fluorescence intensity under 310nm excitation light, and calculating the Fe 3+ concentration.
[0018] Beneficial technical effects:
[0019] 1. Different from the traditional hydrothermal method, the present invention uses the low-cost, abundant and easily available marine algae - Porphyra as the carbon source and iodine source, and urea as the nitrogen source and carrier, and prepares iodine-nitrogen doped carbon quantum dots (I,N-CQDs) with high stability and good water solubility through solvent-free pyrolysis, avoiding the shortcomings of the traditional hydrothermal method that requires high temperature, high pressure and a large amount of solvent.
[0020] 2. The I,N-CQDs particles prepared and synthesized by the present invention are evenly distributed, with an average particle size of about 2.6 nm, and all particles are less than 10 nm.
[0021] 3. The I,N-CQDs prepared by the present invention have good fluorescence stability and fluorescence performance, and have good basic conditions and huge potential for application in different fields and different environmental systems.
[0022] 4. The present invention utilizes Fe 3+ Based on the fluorescence quenching characteristics of carbon quantum dots, a Fe 3+ The method has a detection limit as low as 0.89 μM and has been used to detect Fe in environmental samples. 3+ Determination. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is the XRD pattern of I,N-CQDs obtained in Example 1;
[0025] Figure 2 The SEM spectrum, transmission electron microscopy image, and particle size statistical distribution diagram and high-resolution transmission electron microscopy image of I, N-CQDs in Example 1 after freeze-drying, wherein a, b, and c are SEM images of I, N-CQDs after freeze-drying at different angles, d is a transmission electron microscopy image and a particle size statistical distribution diagram in the illustration, and e is a high-resolution transmission electron microscopy image;
[0026] Figure 3 This is the infrared spectrum of I,N-CQDs obtained in Example 1;
[0027] Figure 4 This is the full XPS spectrum of I,N-CQDs obtained in Example 1;
[0028] Figure 5 The ultraviolet absorption spectrum and fluorescence emission spectrum of I,N-CQDs obtained in Example 1 and the fluorescence intensity analysis at different emission wavelengths, wherein a is the ultraviolet absorption spectrum and fluorescence spectrum, and b is the fluorescence intensity analysis diagram at different emission wavelengths;
[0029] Figure 6 The fluorescence intensity graphs of I,N-CQDs obtained in Example 1 under different ionic strengths, pH levels, UV irradiation times and different H2O2 concentrations, wherein a is a fluorescence intensity graph of I,N-CQDs under different ionic strengths, b is a fluorescence intensity graph of I,N-CQDs under different pH levels, c is a fluorescence intensity graph of I,N-CQDs under different UV irradiation times, and d is a fluorescence intensity graph of I,N-CQDs under different H2O2 concentrations;
[0030] Figure 7 The effect of different ions and different substances on the fluorescence intensity of I, N-CQDs obtained in Example 1 and the fluorescence intensity of I, N-CQDs and Fe 3+ The effect of reaction time on fluorescence intensity, where a is the effect of different ions and different substances on the fluorescence intensity of I, N-CQDs, and b is the effect of I, N-CQDs and Fe 3+ Effect of reaction time on fluorescence intensity;
[0031] Figure 8 The I,N-CQDs obtained in Example 1 are on Fe 3+ Fluorescence intensity plots and fluorescence quenching versus Fe concentration range 0-1000 μM 3+ concentration, where a is the concentration of I, N-CQDs in Fe 3+ Fluorescence intensity diagram in the concentration range of 0-1000μM, b is the fluorescence quenching and Fe 3+ Concentration diagram. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] The "room temperature" mentioned in the present invention means 20-30°C unless otherwise specified.
[0038] The present invention provides a method for preparing iodine-nitrogen-doped carbon quantum dots based on a solvent-free pyrolysis method, which specifically comprises the following steps:
[0039] After the laver is cooled with liquid nitrogen, it is ground into powder. The laver powder is mixed with urea and placed in a round-bottom flask and heated in an oil bath at 160-200°C for 1-3 hours under magnetic stirring. After cooling to room temperature, deionized water is added to dissolve the solid (the mass volume ratio of laver, urea, and deionized water is 0.1g:5.0g:30mL), and then it is centrifuged at 3000-6000rpm for 5-15 minutes, and the resulting supernatant is filtered with a 0.22μm microporous filter membrane. The resulting yellow clear solution is dialyzed with deionized water in a 1000Da dialysis bag for 12-48 hours to remove unreacted small molecules or impurities. The solution obtained after dialysis is iodine- and nitrogen-doped carbon quantum dots (I,N-CQDs).
[0040] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0041] All raw materials used in the embodiments of the present invention are purchased from commercial sources. The present invention does not specifically limit the source of laver. As an example, the laver in the embodiments of the present invention is purchased from a market in Zhanjiang City, and other materials and reagents can be purchased from reagent companies.
[0042] Example 1
[0043] After the laver was cooled with liquid nitrogen, it was ground into powder, 0.1g of laver powder was weighed and mixed with 5.0g of urea and placed in a round-bottom flask, and heated in an oil bath at 180°C with magnetic stirring for 2 hours. After cooling to room temperature, 30mL of deionized water was added to dissolve the solid, followed by centrifugation at 4000rpm for 10 minutes, and the supernatant was filtered with a 0.22μm microporous filter membrane. The obtained yellow clear solution was dialyzed with deionized water in a 1000Da dialysis bag for 24h to remove unreacted small molecules or impurities. The solution obtained after dialysis was iodine- and nitrogen-doped carbon quantum dots (I,N-CQDs).
[0044] The XRD pattern of I,N-CQDs prepared in Example 1 is shown in Figure 1 Through XRD analysis of the crystal structure characteristics of I,N-CQDs, it can be seen that a bun-shaped peak appears at a diffraction angle of 20 degrees and a sharp peak appears at 27 degrees, which is the position of the (002) crystal plane of graphene. This shows that the I,N-CQDs prepared by laver are mainly composed of amorphous carbon quantum dots and complete carbon quantum dots.
[0045] like Figure 2 As shown in Figures ac, after vacuum freeze drying, the I,N-CQDs prepared in Example 1 exhibit good dispersibility and are coral-like and flake-like in shape. Figure 2 As shown in Figure d, I,N-CQDs particles are evenly distributed, and the particle size is less than 10nm. According to the particle size distribution statistics (shown in the inset), the minimum particle size of carbon quantum dots is 0.6nm, the maximum particle size is 3.8nm, and most of the particles are around 2.6nm. This fully demonstrates that laver can be used to prepare carbon quantum dots with small and uniform particle size through this preparation method. Figure 2 As shown in Figure e, the carbon quantum dot particles with lattice fringes were analyzed by high-resolution transmission electron microscopy, and the crystal plane spacing was 0.34nm, which belongs to the (002) crystal plane commonly seen in carbon materials, which is consistent with the XRD results.
[0046] The surface functional groups of the I,N-CQDs prepared in Example 1 were analyzed by Fourier transform infrared spectroscopy. Figure 3Several characteristic absorption peaks are shown, including 3439 cm -1 The NH absorption peak at 3434 cm -1 OH absorption peak at 1670 cm -1 C=C peak at 1624cm -1 C=N peak at 1358cm -1 C=O peak at 1229cm -1 C=C peak at 1154cm -1 CO peak at 1079cm -1 The CN deformation peak at 780 cm -1 -NH at 576cm -1 N=N stretching vibration peak at 1463cm -1 The absorption peak at corresponds to the weak out-of-plane bending vibration of the OH bond. These results indicate that there are many hydroxyl and amino groups on the surface of I,N-CQDs, which helps to improve their solubility in water and enables them to be uniformly and stably dispersed in aqueous solution.
[0047] The chemical composition of the I,N-CQDs prepared in Example 1 was characterized by X-ray photoelectron spectroscopy (XPS). Figure 4 As shown in the figure, the XPS full spectrum analysis shows that the elemental composition of I,N-CQDs is mainly composed of four elements: C, O, N, and I, with their proportions being 36.43%, 18.58%, 13.82%, and 1.3%, respectively. These XPS results show that there are abundant doping elements on the surface of I,N-CQDs, which are suitable for most carbon quantum dot application scenarios.
[0048] The optical properties of the I,N-CQDs prepared in Example 1 were analyzed by UV-visible absorption and fluorescence spectroscopy. Figure 5 In figure a, the UV absorption spectrum and fluorescence spectrum of I,N-CQDs are shown, and in figure b, the fluorescence emission spectrum of I,N-CQDs is shown. The blue line in figure a represents the UV absorption spectrum, and there is no obvious absorption peak in the UV-visible region. The black line represents the maximum excitation wavelength, and the red line represents the maximum emission wavelength. Figure 5 Figure b shows that when the excitation wavelength changes, the position of the emission peak and the fluorescence intensity will also change. As the excitation wavelength increases from 250nm to 350nm, the corresponding emission peak fluorescence intensity first increases gradually and then decreases gradually. When the excitation wavelength is 310nm, the corresponding emission peak fluorescence intensity reaches a peak value (λem=370nm), indicating that the maximum excitation wavelength (λex) of the I,N-CQDs sample is 310nm, and the maximum emission wavelength (λem) is 370nm. In addition, within the excitation wavelength range of 250-350nm, the Stokes shift is greater than 60nm, indicating that I,N-CQDs is very effective in detecting Fe3+ The interference of excitation light can be effectively avoided during the process.
[0049] The I,N-CQDs prepared in Example 1 showed fluorescence stability under different ionic strengths, pH levels, UV light irradiation times and different H2O2 concentrations. Figure 6 As shown in (a), when the NaCl concentration increases from 0 to 3 M, the fluorescence intensity of I,N-CQDs remains basically unchanged, indicating that the increase in ionic strength has no effect on the fluorescence properties of I,N-CQDs. Figure 6 Figure b shows the fluorescence intensity of I,N-CQDs at different pH levels. The fluorescence intensity of I,N-CQDs is high and stable between pH 10 and 12, and decreases slightly under acidic conditions, indicating that there are a large number of hydroxyl groups on the surface of I,N-CQDs that react with acids. These results are consistent with previous studies. After irradiation with 365nm UV light for 180 minutes, the fluorescence intensity of I,N-CQDs remained essentially unchanged ( Figure 6 c), which indicates that I,N-CQDs have excellent fluorescence stability. Figure 6 As shown in Figure d, when the H2O2 concentration in the I,N-CQDs system increased from 0 to 500 mM, the fluorescence intensity decreased slightly but gradually stabilized. It can be concluded that I,N-CQDs have good antioxidant properties.
[0050] Based on the excellent fluorescence performance and stability of I,N-CQDs prepared in Example 1, the ability of I,N-CQDs in metal ion detection was evaluated. First, different substances (Na + , K + , Ba 2+ 、Zn 2+ , Ca 2+ 、Ni 2+ , Fe 2 + 、Co 2+ 、Al 3+ Mg 2+ , alanine, L-serine, L-glutamic acid, glycine, L-asparagine, L-cysteine, leucine, urea) on the fluorescence intensity of I,N-CQDs. Figure 7 As shown in a, at an excitation wavelength of 310 nm, only Fe 3+ The fluorescence quenching degree of I, N-CQDs is the largest, and other substances do not cause fluorescence quenching effect on I, N-CQDs, indicating that I, N-CQDs have a strong effect on Fe 3+ Secondly, in order to study the effects of other interfering substances on Fe 3+ The effect of detection on I,N-CQDs+Fe3+ Different interfering substances (Na + , K + , Ba 2+ 、Zn 2+ , Ca 2+ 、Ni 2+ , Fe 2+ 、Co 2+ 、Al 3+ Mg 2+ , alanine, L-serine, L-glutamic acid, glycine, L-asparagine, L-cysteine, leucine, urea), such as Figure 7 As shown in a, other interfering substances have an effect on Fe 3+ The interference of the detection is very small and can be ignored, indicating that I,N-CQDs have a great influence on Fe 3+ The detection has strong anti-interference ability. Finally, the fluorescence intensity of I,N-CQDs was studied as it interacted with Fe 3+ The reaction time was changed to study the relationship between I,N-CQDs and Fe 3+ Effect of reaction time on fluorescence intensity ( Figure 7 b). The results show that Fe 3+ After reacting with I,N-CQDs for 1 min, the fluorescence intensity dropped sharply. As the reaction time increased, the fluorescence intensity hardly changed, indicating that the fluorescence of I,N-CQDs can be removed by Fe within 1 min. 3+ Complete quenching. In order to ensure the completeness of the quenching reaction, 10 min was selected as the response time in this study. The above results show that I, N-CQDs have excellent performance and can be used as a detection method for trace Fe 3+ An effective fluorescence sensor.
[0051] At an excitation wavelength of 310 nm, the I,N-CQDs solution prepared in Example 1 was subjected to the addition of Fe 3+ The fluorescence intensity was monitored in the concentration range of 0-1000 μM to study the quenching of I,N-CQDs and Fe 3+ The relationship between the concentration. Figure 8 As shown in a, with Fe 3+ With the increase of concentration, the inhibitory effect of I,N-CQDs on the fluorescence intensity increases. Figure 8 Figure b shows the quenching efficiency F0 / F of I,N-CQDs, where F and F0 are in the presence and absence of Fe, respectively. 3+ The fluorescence intensity of I,N-CQDs is calculated by regression equation F0 / F=0.00179[Fe 3+ ]+1.15423(R 2 =0.999), it can be seen that in the range of 0-400μM, F0 / F and Fe 3+The concentration showed a significant linear correlation. The limit of detection (LOD) was 0.89 μM (LOD = 3σ / k, where σ is the standard deviation of the blank sample and k is the slope of the linear equation). This LOD is lower than most values reported in the literature.
[0052] Example 2
[0053] Same as Example 1, except that the oil bath is heated to 160°C.
[0054] Example 3
[0055] Same as Example 1, except that the oil bath is heated to 170°C.
[0056] Example 4
[0057] Same as Example 1, except that the oil bath is heated to 190°C.
[0058] Example 5
[0059] Same as Example 1, except that the heating temperature in the oil bath is 200°C.
[0060] Example 6
[0061] Same as Example 1, except that the heating time in the oil bath is 1 hour.
[0062] Example 7
[0063] Same as Example 1, except that the heating time in the oil bath is 3 hours.
[0064] Example 8
[0065] Same as Example 1, except that the centrifugal speed is 3000 rpm.
[0066] Example 9
[0067] Same as Example 1, except that the centrifugal speed is 5000 rpm.
[0068] Example 10
[0069] Same as Example 1, except that the centrifugal speed is 6000 rpm.
[0070] Embodiment 11
[0071] Same as Example 1, except that the centrifugation time is 5 minutes.
[0072] Example 12
[0073] Same as Example 1, except that the centrifugation time is 15 minutes.
[0074] Example 13
[0075] Same as Example 1, except that the purification time using the 1000Da dialysis membrane is 12 hours.
[0076] Embodiment 14
[0077] Same as Example 1, except that the purification time using the 1000Da dialysis membrane is 36 hours.
[0078] Embodiment 15
[0079] Same as Example 1, except that the purification time using the 1000Da dialysis membrane is 48 hours.
[0080] The I,N-CQDs prepared in Example 2 to Example 15 were tested for their effects. The test results were similar to those in Example 1. The I,N-CQDs obtained in Example 2 to Example 15 had uniform particle sizes, all less than 10 nm. They showed excellent fluorescence performance and stability under different ionic strengths, pH levels, UV irradiation times, and different H2O2 concentrations, and had strong anti-interference properties. 3+ Highly selective detection.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing iodine-nitrogen doped carbon quantum dots based on solvent-free pyrolysis, characterized in that: The following steps are involved: The laver was ground into powder and then mixed with urea, heated in an oil bath under magnetic stirring, then cooled to room temperature, deionized water was added to dissolve the solid, centrifuged, filtered, and dialyzed to obtain iodine-nitrogen doped carbon quantum dots; The mass volume ratio of the laver, urea and deionized water is 0.1 g:5.0 g:30 mL; The oil bath is heated at a temperature of 160-200° C. for a time of 1-3 hours.
2. The method according to claim 1, characterized in that The method of grinding the laver into powder is to use liquid nitrogen to cool the laver and then grind it into powder.
3. The method according to claim 1, characterized in that The centrifugation is performed at a speed of 3000-6000 rpm and for a time of 5-15 minutes.
4. The method according to claim 1, characterized in that: The filtration is performed using a 0.22 μm microporous filter membrane.
5. The method according to claim 1, characterized in that The dialysis is performed using a 1000Da dialysis membrane; the dialysis time is 12-48 hours.
6. Iodine-nitrogen-doped carbon quantum dots prepared by the method for preparing iodine-nitrogen-doped carbon quantum dots based on solvent-free pyrolysis as described in any one of claims 1 to 5.
7. The iodine-nitrogen doped carbon quantum dots as claimed in claim 6 are used as fluorescent probes in Fe 3+ Applications in the field of detection.
8. A method for detecting Fe 3+ The method is characterized in that Add the iodine-nitrogen doped carbon quantum dots as described in claim 6 to the sample to be tested, shake it and let it stand, test the fluorescence intensity under the excitation light of 310 nm, and calculate the Fe 3+ concentration.
Citation Information
Patent Citations
Carbon quantum dot prepared from marine food product as well as detection method and application thereof
CN106892419A
Iodine-doped carbon quantum dot as well as preparation method and application thereof
CN114369458A
Blue-purple phosphorescent carbon quantum dots and preparation method thereof
CN115197699A